2022
DOI: 10.1038/s41598-021-04153-3
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharide alleviates the growth inhibition caused by physcion and synergistically enhances resilience in maize seedlings

Abstract: The use of biopesticides has gradually become essential to ensure food security and sustainable agricultural production. Nevertheless, the use of single biopesticides is frequently suboptimal in agricultural production given the diversity of biotic and abiotic stresses. The present study investigated the effects of two biopesticides, physcion and chitosan-oligosaccharide (COS), alone and in combination, on growth regulation and antioxidant potential of maize seedlings by seed coating. As suggested from the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In addition, the reduction of MDA content indirectly indicates that the use of AVM−γ-CD–MOFs did not negatively affect the integrity of cell membranes and improved the stress tolerance of cotton. Similarly, combined physcion and chitosan oligosaccharide applications had the same positive effect on lipid peroxidation and cell membrane damage in maize …”
Section: Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the reduction of MDA content indirectly indicates that the use of AVM−γ-CD–MOFs did not negatively affect the integrity of cell membranes and improved the stress tolerance of cotton. Similarly, combined physcion and chitosan oligosaccharide applications had the same positive effect on lipid peroxidation and cell membrane damage in maize …”
Section: Results and Discussionmentioning
confidence: 84%
“…Similarly, combined physcion and chitosan oligosaccharide applications had the same positive effect on lipid peroxidation and cell membrane damage in maize. 59 Acaricidal Activity. P. citri (McGregor) is an important acaricide with multiple hosts, particularly citrus.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Liu et al (2021) reported that COS could significantly increase the antioxidant enzyme (POD, SOD, and PPO) activity to promote the growth of wheat. Li et al (2022b) found that the application of physcion and COS combination is more effective in facilitating the SOD, POD activities of the maize plants, resulting in plants with high stress resistance. Ou et al (2022) reported that COS could enhance the antioxidant activity of SOD and POD in tea plants.…”
Section: Effect On the Antioxidant Enzyme Activitymentioning
confidence: 97%
“…They suggested that chitosan alleviated the inhibitory effects of salt stress and improved plant growth. Li et al (2022) evaluated the effect of chitosan oligosaccharide in combination with physcion on maize seedling growth and reported positive outcomes. They suggested the combined application of these two as a seed-coating material to alleviate stress tolerance.…”
Section: Plant Growth and Development Under Chitosan Applicationmentioning
confidence: 99%